Meningkatkan Profesionalisme Guru Dalam Menetapkan Kriteria Ketuntasan Minimal (KKM) Melalui Kegiatan Workshop di MTS Al-Ma’arif Rancalutung Pabuaran Serang - Sahruli Sahruli (Lembaga Pengembangan Kinerja Dosen, 2022)
This School Action Research was carried out on the basis of field facts that the author found that there were still many madrasah teachers who were still unable and proficient in setting the Minimum Completeness Criteria (KKM) required in the implementation of the Madrasah Curriculum at MTs Al-Ma'arif Rancalutung. This condition can be seen as a finding when carrying out a teacher's duties, especially in carrying out learning evaluations, both end of semester exams and madrasa exams. The expected goal of this school action research is that teachers at MTs Al-Ma'arif Rancalutung can establish Minimum Completeness Criteria and this workshop can improve the ability of madrasa teachers in preparing KKM. This school action research was conducted at MTs Al-Ma'arif Rancalutung with a total of 15 subject teachers, while the implementation of this action research consisted of two cycles. The results of this study indicate an increase in the ability of teachers when setting Minimum Completeness Criteria and this workshop is effective as an approach used to increase teachers' abilities in setting minimum completeness criteria because teachers are more active and a growing sense of responsibility for setting minimum completeness criteria in each subject that taught.